Membangun Motivasi Ibu Rumah Tangga: Partisipasi dalam Kegiatan Pengajian di Masjid As-Syukur Desa Grujugan Kecamatan Larangan Kabupaten Pamekasan - Maulidina, Nurul; Setyawan, Agung; Citrawati, Tyasmiarni; Hadikusuma, M. F. (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2024)
The religious study group at the As-Syukur Ta'lim Assembly serves as a platform for housewives in Grujugan Village to gather and deepen their religious knowledge. This assembly aims to instill good morals and uphold the commandments of ma'ruf (promoting good) against evil. This research uses a descriptive qualitative method, with data collected through observation and interviews. The respondents interviewed include the head of the As-Syukur Ta'lim Assembly and several female members of the congregation. Data analysis in this study involves data reduction, data presentation, and drawing conclusions. The research findings conclude that the motivation for housewives' participation in the As-Syukur Ta'lim Assembly activities consists of intrinsic and extrinsic motivation. Intrinsic motivation includes the desire to study religion, improve the quality of worship, and strengthen social bonds. Extrinsic motivation arises from peer influence and contributions made by the Ta'lim Assembly, which are allocated to religious and social activities. Supporting factors for the participation of housewives in the As-Syukur Assembly's study sessions include the awareness of seeking knowledge, as well as engaging methods and relevant lecture materials.